Mulheres jacobitas e silêncios da história: a revolta de 1745 e roupas femininas desafiantes - Zimmer, Marina Pellanda (Universidade do Vale do Rio dos Sinos, 2020)
This paper proposes to explore an aspect of History of Women, previously silenced by traditional historiography and, at the same time, understand how Fashion is relevant in Society behavior and beliefs. Scottish jacobite women from the 1745 uprising were silenced by History for a very long time, and just recently began to be studied. This research study those women, the clothes they wore and how that demonstrated their strong connection with their culture. Scottish indumentary and its History also have an important role in this research. Furthermore, the fashion brand Alexander McQueen is analyzed, and its history reviewed, serving as a parameter for a Fashion Collection, given its connection with the approached subjects. A combination between the Inductive and Dialectic Methods has been used as scientific method. The development of the Fashion Collection was undertaking using the concepts of Strategic Design. This study sought to draw a panorama about revolutionary Scottish women of the period, despite significant gaps in the literature about this theme, thus contributing to Women History.
Keywords: Mulheres jacobitas; Silenciamento feminino; Vestimenta escocesa; Alexander McQueen; Jacobite women; Feminine silencing; Scottish indumentary